Association of total cholesterol to high-density lipoprotein cholesterol ratio with diabetes risk: a retrospective study of Chinese individuals - Zhang, Zhiqiang; Chen, Hejun; Chen, Lei; Liang, Wenyan; Hu, Tenglong; Sun, Na; Zhao, Yangyu; Wei, Xiqing (Scientific reports, 2025)
A common complication of type 2 diabetes is hypercholesterolemia in many patients. It is still unclear, nevertheless, how high-density lipoprotein cholesterol ratio (TC/HDL-C), total cholesterol, and diabetes are related. The purpose of this study is to look at the prediction ability and causal relationship between TC/HDL-C and diabetes. This study included 117,268 subjects who were undergoing physical examinations. The subjects were grouped into four equal groups according to the TC/HDL-C quartiles; the main outcome was the occurrence of diabetes events. TC/HDL-C is calculated as total cholesterol divided by high-density lipoprotein cholesterol. In 3.1 years (± 0.95) of follow-up, 795 women (0.68%) and 1,894 men (1.62%) received new diabetes diagnoses. TC/HDL-C is an independent predictor of new-onset diabetes, according to multivariable Cox regression analysis (HR 1.27 per SD increase, 95% CI: 1.09–1.48, P for trend < 0.001). It turned out that a cutoff value of 3.55 (area under the curve 0.64, sensitivity 0.66, specificity 0.56), was ideal for TC/HDL-C in predicting new-onset diabetes. A subgroup analysis demonstrated that the younger population had a significantly higher risk of TC/HDL-C-related diabetes than the middle-aged group (interaction P < 0.05). After controlling for confounding variables, this Chinese cohort study reveals a direct correlation between TC/HDL-C and diabetes, with a stronger independent association observed in younger and middle-aged individuals.